GOOD GOVERNMENT GOVERNANCE IN OVERCOMING POVERTY-FEMINIZATION - Fathia, Syaharani Noer; Majidah, Rona; Octary, Ayu Dwiny; Rohman, Fatkhur (Faculty of Economics and Business, 2025)
This study aims to explore the role of good government governance as a theoretical framework in overcoming Poverty-Feminization. This objective stems from the significant slowdown in achieving Sustainable Development Goal 5 (SDG 5) on gender equality, with a progress rate of only 61.5%, categorized as far or very off track as of 2023. The research gap in this study is the in-depth study of poverty, not just poverty as in previous studies in general, but also poverty that is feminized, or centred on and directed at women. Most previous studies tend to highlight poverty from a macroeconomic perspective, such as national income, unequal distribution of resources, or indicators of overall societal welfare without specifically considering gender dimensions. However, poverty has different characteristics when experienced by women, particularly in social, economic, and cultural contexts that place women in a more vulnerable structural position. This study employs a qualitative approach using the literature review method to identify and synthesize empirical findings. Based on a literature review of 16 articles which relevant to the issue risen, it was found that the implementation of good government governance encompassing public participation, accountability, and the rule of law can effectively contribute to reducing the rate of Poverty-Feminization in lower-middle income countries.